Visual Content Analysis of STEM-Related Content in Indonesian Vocational High Schools Biology Textbooks - Bevo Wahono; Ima Masafatus Sholihah; Erlia Narulita (Universitas Pendidikan Indonesia, 2023)
This research aims to analyze the characteristics of STEM-related visual content in Indonesian Vocational High School biology textbooks. Biology textbooks have been adapted to the latest scientific and technological advances and curriculum demands and declared feasible. However, some distributed biology textbooks in Indonesia may need to be improved and have various areas for improvement and problems. This study used NVivo to perform a descriptive statistic comprising 197 visual samples from the two biology textbooks. The results have shown that the type of